3D Bioprinting to Fabricate Living Microalgal Materials. Issue 12 (December 2021) - Kumar, Vinod; Vlaskin, Mikhail S.; Grigorenko, Anatoly V.
Abstract : 3D bioprinting to fabricate live microalgal materials is an impending technological transformation in the field of microalgal biotechnology. Balasubramanian et al . have demonstrated 3D bioprinting using alginate hydrogel encapsulation to create unique photosynthetically active microalgal biomaterials that are biodegradable, regenerative, and eco-friendly.